The modulation of mRNA levels of MAOA by electroacupuncture and psychotherapy in patients with pathological internet use - Dai, Yu; Zhang, Chenchen; Zhang, Lingrui; Wen, Chao; Zhu, Tianmin (Frontiers in Psychiatry, 2022)
Objective: Both electroacupuncture and psychotherapy are effective interventions for pathological internet use (PIU). But the underlying mechanisms of those interventions for PIU remain unknown. Neurobiological studies have revealed the Monoamine oxidase type A (MAOA) plays an important role in the progress of addiction diseases. In addition, our earlier research demonstrated mRNA levels of MAOA is related to PIU. Hence, the aim of this study was to detect the relative expression of mRNA of MAOA gene in the EA group and the PT group before and after treatment for exploring the effects of electroacupuncture and psychotherapy on mRNA levels of MAOA in patients with PIU. Methods: A total of 60 PIU patients were included for the present study. These patients were randomly divided into two groups: electroacupuncture (EA) group and psychotherapy (PT) group. Baihui, Sishencong, Hegu, Neiguan, Shenmen, Taichong, Sanyinjiao and Xuanzhong were selected for acupuncture in the EA group, while group psychotherapy combined with individual psychotherapy was used for intervention in patients in the PT group. Young’s Internet addiction Test (IAT), Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Barratt Impulse Scale (BIS-11) and Pittsburgh Sleep Quality Index (PSQI) were used to observe the severity of Internet addiction, mental status, sleep quality and impulsive trait of patients with PIU before and after treatment; and assessed the effects of electroacupuncture and psychological intervention in mRNA levels of MAOA in patients with PIU. Results: Both interventions can improve severity of Internet addiction, mental status, sleep quality and impulsive trait of PIU patients. After treatment the expression of MAOA mRNA was elevated with patients in the PT group, and EA has little effect on MAOA gene expression in patients with PIU. Conclusion: The present study indicated upregulated expression of MAOA mRNA in patients with PIU after psychotherapy, suggesting that neurobiological changes may be the underlying mechanisms of psychotherapy treatment on internet addiction.